Manajemen Mutu Sebagai Langkah Strategi (Studi pada Jurusan Manajemen FEB UB) - Nugraha, Aditya Dwi (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to identify the extent of quality management in becoming a part of strategies taken by Management Department of FEB UB. This qualitative descriptive research use deep data retrieval technique. The data of this study are obtained from interviews on Quality Assurance Unit staff and Management Department staff of FEB UB, documentation, study on the reports of Management Department, and observation on activities related to quality management. The results of this study indicate that quality management system is an integral part of the strategic management applied by Management Department of FEB UB. Quality management is a strategy step that is planned and evaluated in an integrated manner using strategic planning and evaluation applied by Management Department of FEB UB.Keywords: Quality Management, Strategy Management